Dogathon At UPM - The Star, (2008)
STUDENTS of the Veterinary Medicine Faculty of Universiti Putra Malaysia (UPM) will be organising a dogathon at Bukit Ekspo UPM Serdang on Aug 10 from 7am to 2pm The event is to raise funds for their catch neuter release project and it will be making its mark in the Malaysia Book of Records as well.